Innovative anthelmintic based on mechanochemical technology and their efficacy against parasitic infection of sheeps - Marchenko, Victor A; Khalikov, Salavat S; Vasilenko, Yury A; Ilyin, Mikhail M; Kravchenko, Irina A (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Solubility and bioavailability are crucial for maximizing the activity of an antiparasitic drug. This study aimed to develop a combined preparation for antiparasitic medicines using ivermectin (Iver), fenbendazole (FBZ), and triclabendazole (TBZ), considering their solubility, bioavailability, and activity. Materials and Methods: Innovative preparations in solid dispersions (SD) were obtained using the joint mechanical processing of drug substances with polyvinylpyrrolidone (PVP) in an LE-101 roller mill. The preparations’ efficacy was studied in 140 sheep spontaneously infected with gastrointestinal Strongylata, Dicrococelium dendriticum, Moniezia expansa, and Melophagus ovinus. The preparations were given individually to the sheep in the form of an aqueous suspension orally. Their effectiveness was evaluated using intravital and postmortem parasitological examinations. Results: The results confirmed the increase in solubility of substances by 13–29 times. The experiments have shown the high efficacy of SD composition of FBZ/Iver/PVP (1/1/9) containing FBZ (at 3.0 mg/kg b/w) and Iver (at 0.2 mg/kg b/w) when used against gastrointestinal Strongylates and M. expansa (95.8% and 100%, respectively), to a lesser extent against M. ovinus (38.5%). The SD composition of TBZ/Iver/PVP (1/1/9) of TBZ (at 3.0 mg/kg b/w) and Iver (at 0.2 mg/kg b/w) showed a high efficacy against gastrointestinal Strongylata and D. dendriticum (96.8% and 100%, respectively) and less activity against M. ovinus (61.6%). Conclusion: The high parasiticidal activity of SD based on FBZ, TBZ, and Iver in comparison with initial substances is explained by the formation of inclusion complexes of these substances with PVP when SD is dissolved in water and the synergistic effect of the active substances of the preparations. The resulting complexes have increased solubility in water and bioavailability. The use of such an SD suggests a significant reduction in the dosages of FBZ and TBZ without losing parasiticidal activity. J. Adv. Vet. Anim. Res., 7(4): 718-725, Dec 2020 http://doi.org/10.5455/javar.2020.g473